2014
DOI: 10.4172/2167-0420.1000140
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Husbands’ Participation on Birth Preparedness and Complication Readiness in Enderta Woreda, Tigray Region, Ethiopia, 2012

Abstract: Background: Male involvement in reproductive health has been promoted as a promising new strategy for improving maternal and child health. The promotion of husband participation in the process of antenatal care and in preparations for the delivery is very important.Objective: To assess husband participation on birth preparedness and complication readiness in Enderta Woreda, Tigray region, Ethiopia, 2012. Methods:A community based cross-sectional study was conducted among 376 husbands whose wives was delivered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 9 publications
3
6
1
Order By: Relevance
“…This is evidenced by high maternal and child morbidity and mortality in Amhara regional state in which the study area is found. This finding is in line with study report from Tigray region, Ethiopian and Central Ghana [28,29]. This might be now a day's almost all African countries have implemented same strategies that can increase the engagement of husbands in maternal health services through extensive work of health extension workers and health care providers.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This is evidenced by high maternal and child morbidity and mortality in Amhara regional state in which the study area is found. This finding is in line with study report from Tigray region, Ethiopian and Central Ghana [28,29]. This might be now a day's almost all African countries have implemented same strategies that can increase the engagement of husbands in maternal health services through extensive work of health extension workers and health care providers.…”
Section: Discussionsupporting
confidence: 87%
“…Husbands who had attended secondary and above education were 1.93 times more likely to accompany their wives in ANC than those who had no formal education. Similar studies in Nepal, Central Ghana and Goba town Ethiopia have found that education level is an important factor for husband antenatal care attendance [14,18,29]. This may be related to as people more educated they could easily understood the importance of husband attendance in maternal health care service including antenatal care.…”
Section: Discussionsupporting
confidence: 56%
“…Male partner’s financial readiness for costs related to delivery of the baby varied significantly in LMICs with the lowest (15.7%) reported from Ethiopia [ 84 ] and the highest (92.7%) indicated in Nigeria [ 5 ]. The pooled estimate of saving money for delivery was 45.7%.…”
Section: Discussionmentioning
confidence: 99%
“…Interviewer administered questionnaires were conducted for the quantitative study. The questionnaire was adapted from the survey tools developed by JHPIEGO Maternal and Neonatal Health Program [15]. It is divided into four parts.…”
Section: Data Collection Toolmentioning
confidence: 99%